2019
DOI: 10.1186/s12957-019-1754-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the intestinal microbiome in colorectal cancer surgery outcomes

Abstract: ObjectivesGrowing evidence supports the role of the intestinal microbiome in the carcinogenesis of colorectal cancers, but its impact on colorectal cancer surgery outcomes is not clearly defined. This systematic review aimed to analyze the association between intestinal microbiome composition and postoperative complication and survival following colorectal cancer surgery.MethodsA systematic review was conducted according to the 2009 PRISMA guidelines. Two independent reviewers searched the literature in a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 45 publications
1
34
0
2
Order By: Relevance
“…Our findings underline the multifactorial pathogenesis of AL. Low intraoperative blood pressure, liberal perioperative fluid management, and the gut microbiome seem to contribute to its occurrence [21, 22]. Consequently, a trial protocol assessing perfusion as well as multiple other factors, such as mechanic stability and tension, as risk factors for AL was recently published [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings underline the multifactorial pathogenesis of AL. Low intraoperative blood pressure, liberal perioperative fluid management, and the gut microbiome seem to contribute to its occurrence [21, 22]. Consequently, a trial protocol assessing perfusion as well as multiple other factors, such as mechanic stability and tension, as risk factors for AL was recently published [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, they clustered taxonomic groups instead of unique bacterial genomes and did not explore potential relationships between CAGs and host phenotypes. Since then, the concept of co-abundance group or co-abundance network has been applied in several dozens of microbiota studies [ 51 73 ]. Most of these studies [ 51 64 ], including Claesson et al [ 50 ], first collapsed unique bacterial genomes into taxonomic units and then clustered taxonomic units into CAGs.…”
Section: Ecological Guilds As Units For Microbiome Data Reductionmentioning
confidence: 99%
“…Most of these studies [ 51 64 ], including Claesson et al [ 50 ], first collapsed unique bacterial genomes into taxonomic units and then clustered taxonomic units into CAGs. The remaining publications [ 65 73 ] grouped unique genomes, operational taxonomic units (OTUs), or amplicon sequence variants (ASVs) into CAGs. However, these studies [ 65 73 ] did not treat CAGs as functional units nor directly investigated potential relationships between CAGs and host phenotypes.…”
Section: Ecological Guilds As Units For Microbiome Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the important lifestyle risk factors for cancer like obesity (6), smoking (7), diet (8) and alcohol (9) can cause perturbations in the microbial composition as well. Emerging evidence suggests that host microbial signatures may be able to predict some incipient cancers (10), modulate response to and toxicity of cancer immunotherapy (11)(12)(13) and even correlate with survival in specific cancers (14,15). Extensive exploration of the role of the microbiome in cancer evolution has demonstrated that while the microbiome can affect cancer cells themselves, it can also modulate the cancer immunosurveillance.…”
Section: Introductionmentioning
confidence: 99%